On representation formula for solutions of Hamilton‐Jacobi equation for some types of initial conditions - Gudynas, G. (Mathematical Modelling and Analysis, 2001)
This article investigates the representation formula for the semiconcave solutions of the Cauchy problem for Hamilton‐Jacobi equation with the convex Hamiltonian and the unbounded lower semicontinous initial function. The formula like Hopf‘s formula is given by forming envelope of some fundamental solutions of the equation.Apie Hamiltono-Jakobo sprendinių išraiškas tam tikroms pradinėms sąlygomsSantrauka. Nagrinėjami Kosi uždaviniai lygtimssu pradine sąlygaIškilių hamiltonianų atveju yra užduotos formules Koši uždavinių sprendiniams: pirmosios lygties atveju, kai ϕ(x) yra pusiau tolydi iš apačios irantrosios lygties atveju pradinė funkcija tolydi Lipšico prasme ir yra laužtė, trečiosios lygties atveju pradinė funkcija aprėžta ir dalimis pastovi.First Published online: 14 Oct 2010